Implementasi Pendidikan Pesantren dalam Keluarga sebagai Tanggungjawab Orangtua Mendidik Anak - Pamungkas, Maulana Al Bana; Anshory, Muhammad Isa (TSAQOFAH, 2024)
This article discusses the application of education that pesantren instill in their students based on Surah Luqman verses 12 and 13. The aim is to remind parents about the responsibility of educating children and to help provide insight into what things need to be instilled and accustomed to children in their daily lives. This research uses literature study method and descriptive qualitative with data collection techniques through observation. Implementation of Pesantren Education in the Family as the Responsibility of Parents to Educate Children is able to be one solution in providing insight to parents about what is very important to give to children both from an early age until children grow up. With the hope that children who have been sent to school by their parents remain in good habits and do not forget their life while in boarding school.